PERBEDAAN PENGARUH AEROBIC EXERCISE DAN GAZE STABILITY EXERCISE TERHADAP RESIKO JATUH PADA LANSIA - Mohamad Rifqi S. Panto; Tri Laksono; Noor Sadhono Kurniaji (Bajang Institute, 2025)
Introduction: Elderly are individuals over 60 years old who experience the aging process as part of the life cycle. At this stage, various interrelated physical, psychological and social changes occur, potentially causing health problems; one of which is the risk of falls. Trainings such as aerobic exercise and gaze stability exercise can be given as a solution to overcome this condition. This study aims to analyze the different effects between aerobic exercise and gaze stability exercise on the risk of falls in the elderly.Method: This research employed a quasi-experimental method in 2 groups. Each group consisted of 20 respondents. Group I received aerobic exercise treatment and group II received gaze stability exercise treatment. All groups participated in training 3 times a week for 4 weeks. The measuring instruments used were the Time Up and Go Test (TUGT) and the Morse Fall Scale (MFS). The measurements were done at the first meeting before being given training and at the last meeting after being given training.Results: The results of the Mann Withney test in both groups showed that group I that took part in Aerobic Exercise experienced a decrease in the Time Up and Go Test (TUGT) score from 22.75 ± 3.94 in the pre-test to18.83 ± 3.43 in the post-test, with a difference of 3.92 ± 1.15. Group II that did the Gaze Stability Exercise showed a greater decrease, with a pre-test score was 21.89 ± 5.81 and post-test was 16.37 ± 4.39, with a difference of 5.51± 1.76.Conclusion: There is a different effect between aerobic exercise and gaze stability exercise on the risk of falls in the elderly.